2005
DOI: 10.1016/j.ydbio.2004.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Activin receptor-like kinase 2 and Smad6 regulate epithelial–mesenchymal transformation during cardiac valve formation

Abstract: Epithelial-mesenchymal transformation (EMT) occurs during both development and tumorigenesis. Transforming growth factor beta (TGFbeta) ligands signal EMT in the atrioventricular (AV) cushion of the developing heart, a critical step in valve formation. TGFbeta signals through a complex of type I and type II receptors. Several type I receptors exist although activin receptor-like kinase (ALK) 5 mediates the majority of TGFbeta signaling. Here, we demonstrate that ALK2 is sufficient to induce EMT in the heart. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
103
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 82 publications
(112 citation statements)
references
References 50 publications
7
103
1
1
Order By: Relevance
“…ALK2 has the highest sequence homology with ALK1 (ten Dijke et al, 1993). Further, ALK1 and ALK2 bind common ligands, interact with common RII subtypes, and mediate TGFb-associated function (Attisano et al, 1993;Ebner et al, 1993a, b;Miettinen et al, 1994;Ward et al, 2002;Goumans et al, 2003;Lebrin et al, 2004;Blanco et al, 2005;Desgrosellier et al, 2005). Using qRT-PCR, we found that ALK2 was expressed at high levels in PCa cells, and was over fourfold higher than ALK5 in both PC3 and PC3-M cells (Figure 5a).…”
Section: Eng Promotes Smad1 Signalingmentioning
confidence: 74%
“…ALK2 has the highest sequence homology with ALK1 (ten Dijke et al, 1993). Further, ALK1 and ALK2 bind common ligands, interact with common RII subtypes, and mediate TGFb-associated function (Attisano et al, 1993;Ebner et al, 1993a, b;Miettinen et al, 1994;Ward et al, 2002;Goumans et al, 2003;Lebrin et al, 2004;Blanco et al, 2005;Desgrosellier et al, 2005). Using qRT-PCR, we found that ALK2 was expressed at high levels in PCa cells, and was over fourfold higher than ALK5 in both PC3 and PC3-M cells (Figure 5a).…”
Section: Eng Promotes Smad1 Signalingmentioning
confidence: 74%
“…In addition, BMPs have the ability to redirect the differentiation of connective tissue progenitor cells [33][34][35] to orchestrate an endothelial-to-mesenchymal transition in these cells, often through inflammatory cell intermediates [36][37][38][39][40] . Interestingly, misexpression of constitutively active ACVR1/ALK2, a BMP type-I receptor and the gene mutated in fibrodysplasia ossificans progressiva, is sufficient to stimulate an endothelialto-mesenchymal transformation in endothelial cells of the heart 41 . Notably, BMP4, as well as hypoxia and inflammatory cytokines-conditions and factors that are present in the earliest preosseous lesions of heterotopic ossification-upregulate Tie2 in endothelial cells, which contributes to the angiogenic response 39,42 .…”
Section: Discussionmentioning
confidence: 99%
“…TBRII can also interact with another type I receptor, ALK2 (Ebner et al, 1993). ALK2 has been implicated in mediating TGF␤-stimulated EMT in AV cushion endocardial cells (Lai et al, 2000;Desgrosellier et al, 2005) and cultured NMuMG breast cancer epithelial cells (Miettinen et al, 1994). These data suggest that TGF␤ may signal by the activation of ALK5 or ALK2.…”
Section: Introductionmentioning
confidence: 92%
“…Activity of Smad6 protein produced by viral infection was determined by its ability to decrease Smad1-dependent alkaline phosphatase activity in C3H10T1/2 cells (McDonnell et al, 2001). Data regarding activity of viral constructs have been reported (Desgrosellier et al, 2005).…”
Section: Pe Explants Infected With Adenovirusmentioning
confidence: 99%